Sex and body weight are major determinants of venlafaxine pharmacokinetics - Schoretsanitēs, Geōrgios; Haen, Ekkehard; Hiemke, Christoph; Fay, Bianca; Unholzer, Sandra; Correll, Christoph U.; Gründer, Gerhard; Paulzen, Michael (International clinical psychopharmacology, 2018)
We assessed the effect of body weight and BMI on plasma concentrations of venlafaxine (VEN), O-desmethylvenlafaxine (ODVEN), active moiety (AM=VEN+ODVEN), and dose-corrected plasma concentrations (C/D). A database containing concentrations of VEN and ODVEN including 737 of 1594 eligible patients was analyzed. Analyses included sex, body weight, and BMI as well as concentrations of VEN, ODVEN, AM, and C/D. A positive correlation was detected between body weight and daily dosage (rs=0.168, P<0.001). A negative correlation was found between body weight and AM (rs=-0.124, P=0.001) and ODVEN (rs=-0.137, P<0.001). Negative correlations were also found between body weight and C/D ratios (C/D VEN: rs=-0.134, P<0.001, C/D ODVEN: rs=-0.239, P<0.001, C/D AM: rs=-0.256, P<0.001). No correlations were detected between BMI and concentrations for VEN, ODVEN, and AM. Comparing low-BMI (<20 kg/m²), medium-BMI (20-29.9 kg/m²), and high-BMI (≥30 kg/m²) groups, higher values of some pharmacokinetic variables in the lower BMI group did not remain significant after controlling for sex. Women had higher VEN, ODVEN, AM, and C/D values for AM, VEN, and ODVEN than men (P<0.001 for all comparisons). Our results highlight the role of different pharmacokinetically relevant parameters and foremost of sex as mediators for the effect of BMI on VEN metabolism.
Gesehen am 28.04.2020